Perkembangan Perolehan Kompetensi Pedagogi Mahasiswa Pendidikan Teknik di Fakultas Teknik UNY - Pardjono Pardjono; Soenarto Soenarto; Wardan Suyanto; Putu Sudira; Edy Purnomo (Department of Mechanical Engineering Education, 2019)
This research aims to reveal the extent of pedagogical-competence of Universitas Negeri Yogyakarta's students as prospective vocational teachers. It will serve as a measure of their readiness to become vocational teachers. The research method was a quantitative approach with a descriptive method to present the pedagogical-competence profile of the students from each study program. The research population was students from several educational study programs, namely Electronics, Mechanical, and Automotive. Samples of 175 students were taken from each study program's class. The pedagogical competence was evaluated using test questions which instruments have been validated by experts. The result shows that the average competence is 50,24. To breakdown this finding, the averages of pedagogical-competence are 44,71 and 50,60 for students in the 3rd and 5th semester, respectively. The comparison data for the averages of the 3rd to 5th-semester students in each study programs are as follows: Electronics are 54,80 to 46,45; Mechanical are 50, 24 and 54,91; and Automotive are 24,18 to 50,72Penelitian ini bertujuan untuk mengungkap seberapa jauh kompetensi pedagogik mahasiswa calon guru teknik di Universitas Negeri Yogyakarta sebagai ukuran kesiapan mereka untuk menjadi guru kejuruan. Metode penelitian menggunakan pendekatan penelitian kuantatif dengen metode deskriptif untuk menunjukkan profil kompetensi pedagogi dari mahasiswa dari masing-masing program studi. Populasi penelitian adalah mahasiswa Prodi PT. Elektronika, PT. Mesin, dan PT. Otomotif. Sampel diambil masing-masing prodi satu kelas yang berjumlah 175 mahasiswa. Kompetensi pedagogik diukur melalui tes dengan instrumen soal yang telah divalidasi oleh ahli. Hasil penelitian menunjukkan bahwa rerata 50,24. Secara rinci rerata mahasiswa semester 3: 44, 71 dan semester 5: 50,60. Prodi Elektronika rerata kompetensi pedagogi mahasiswa semester 3: 54,80 dan semester 5: 46,45; Mahasiswa Prodi PT Mesin, rerata skor semester 3: 50, 24 dan semester 5: 54,91; Mahasiswa Prodi PT Otomotif semester 3: 24,18 dan Semester 5: 50,72